Implementasi Pemilihan Master Berdasarkan Kapasitas Energi Menggunakan Metode Bully Leader Election pada JSN Berbasis LoRa - Ardi Rahmad Hermanto; Mochammad Hannats Hanafi Ichsan; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Wireless Sensor Networks are a series of nodes. That's nodes will make a network. On this network, there is a Master node that works to collect data from all nodes in the network. If the Master node dies then the distribution process will stop. To overcome this we need an algorithm that can overcome these problems. Bully Leader Election applies an algorithm to select leaders with the highest authority among other nodes. The selection is made by checking the energy capacity of each Slave node and then the Slave node with the largest energy capacity is selected as the Master node. The system is implemented on nodes with the LoRa communication protocol. Each selection process will have the same time slot so sending messages do not clash with each other. The choice of the Master node will be influenced by the energy capacity of each node. The more energy that is owned, the life of a node will be longer. By utilizing the energy capacity in the selection of new masters, it is hoped that the possibility of dead Master nodes will be smaller.